The Human Immune Response to Dengue Virus Is Dominated by Highly Cross-Reactive Antibodies Endowed with Neutralizing and Enhancing Activity - Simmons, Cameron (2018)
Antibodies protect against homologous Dengue virus (DENV) infection but can precipitate severe dengue by promoting heterotypic virus entry via Fcγ receptors (FcγR). We immortalized memory B cells from individuals after primary or secondary infection and analyzed anti-DENV monoclonal antibodies (mAbs) thus generated. MAbs to envelope (E) protein domain III (DIII) were either serotype specific or cross-reactive and potently neutralized DENV infection. DI/DII- or viral membrane protein prM-reactive mAbs neutralized poorly and showed broad cross-reactivity with the four DENV serotypes. All mAbs enhanced infection at subneutralizing concentrations. Three mAbs targeting distinct epitopes on the four DENV serotypes and engineered to prevent FcγR binding did not enhance infection and neutralized DENV in vitro and in vivo as postexposure therapy in a mouse model of lethal DENV infection. Our findings reveal an unexpected degree of cross-reactivity in human antibodies against DENV and illustrate the potential for an antibody-based therapy to control severe dengue.